Impact of Risk Management, Safety Culture, and Service Quality on Patient Satisfaction - Sara Mustika Hardy; Vip Paramarta (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
Quality health services are a fundamental aspect in improving the welfare of society. This study aims to analyze the relationship between risk management, safety culture, and service quality on patient satisfaction. The method used was a systematic literature review (SLR) with the PRISMA approach, which reviewed various related studies from 2019 to 2024. Data sources were obtained from Google Scholar and DOAJ, then selected based on relevance criteria to the research topic. The results showed that risk management plays an important role in reducing adverse events and improving patient safety. A strong safety culture, with the implementation of an open incident reporting system and adherence to standard operating procedures, contributes to creating a safe service environment. In addition, service quality, which includes speed of service, friendliness of medical personnel, and adequate facilities, significantly improves patient satisfaction. The conclusion of this study confirms that implementing effective strategies in these three aspects will have a positive impact on the overall quality of health services. These findings can serve as a reference for hospitals in developing health service improvement policies to increase patient satisfaction and public trust in health institutions.